Indoor environment quality and occupant productivity pre-applying COVID-19 measures - Sayed Hassan Abdelmajeed; Mahmoud M. H. Alayis; Abdalla Zahri Amin (Cogent Social Sciences)
Indoor environment quality is considered a vital factor in the success of occupants and in achieving high productivity. In this context, there has been a substantial growth over the past two decades in the studies conducted worldwide examining the relationship between Indoor Environment Quality (IEQ) and occupant’s productivity. This study focuses on the impact of IEQ on Occupant Productivity (OP), as well as its role in facing and overcoming the threats posed by COVID−19. Furthermore, the study paves the way for research on IEQ and OP after returning to work during COVID−19. The researcher conducted a closed-ended questionnaire with telecommunication companies in the Eastern Province of the Kingdom of Saudi Arabia (KSA) from May to December 2019. The total number of completed and collected questionnaires was 385. The data collected were analysed using structural equation modelling technique with the AMOS 23 V software. The findings demonstrate that IEQ has a positive and significant influence on OP. Specifically, the office layout, location and amenities, indoor air quality and ventilation, noise and acoustics, and lighting and day lighting were found to have positive and significant effects on OP. However, biophilia and views were found to have no significant effect on OP. These findings could be used by designers, architectures, facilities managers, and office occupiers to formulate their IEQ strategy to overcome COVID−19 and to increase productivity. The strength of this paper lies in its focus on analyzing and developing a comprehensive and integrated perspective of IEQ elements that contribute to increasing occupants’ productivity upon their return to work during COVID−19. This is accomplished by providing knowledge and training for occupants, in addition to implementing precautionary measures related to the IEQ elements that influence productivity.